"Machine-Dependent": The Lived Experiences of Patients Receiving Hemodialysis in Pakistan. (October 2022) - Shouket, Haseeba; Gringart, Eyal; Drake, Dierdre; Steinwandel, Ulrich
This study aimed to explore the lived experiences of patients receiving maintenance hemodialysis in Pakistan. Purposive sampling was used to recruit 24 patients and six healthcare professionals, each participated in a semi-structured interview. Interpretive Phenomenological Analysis was used to analyze interviews' data. Two superordinate themes, "The experience of hemodialysis" and "The conceptualizations of hemodialysis" as well as six sub-themes were identified. The experience of hemodialysis was related to, the implications of HD procedure on everyday life, social, cognitive, emotional, financial, and occupational influences. While all participants recognized the importance of hemodialysis for their survival, their conceptualizations of the treatment varied. Despite facing multiple challenges, optimism and independence were observed among participants. Stigma related to hemodialysis, and role adaptation, which appear unique to the Pakistani context, highlight a need for tailored interventions designed to enhance and maintain the mental health of patients receiving hemodialysis in Pakistan.